SISTEM NOTIFIKASI BUKA/TUTUP PELINDUNG UNTUK TANAMAN HIDROPONIK BERBASIS RAIN SENSOR MENGGUNAKAN RASPBERRY PI PICO RP2040 - Ike Retna Kusumawati; Wisnu Yudo Untoro (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2022)
Abstract The hydroponic system is a farming technique using water media. Hydroponic cultivation can improve food quality in Indonesia, therefore hydroponic planting requires regular supervision, because hydroponic plants cannot be exposed to direct rain exposure. If exposed to rain continuously, then the plant can wither / die. So cultivators must protect hydroponic plants from rainwater. In the current era, technological developments that are increasingly advanced make cultivators take advantage of this by applying automatic plant protectors that can protect hydroponic plants from exposure to rain. With this automatic plant protector can reduce some of the risks that occur in plants. Therefore, in this study, we designed an automatic system for opening/closing hydroponic plant protectors automatically using the Rain Module Sensor which functions as a rainwater detector and there are supporting sensors, namely a light sensor (Light Dependent Resistor) which functions as light intensity, and to send SMS using a GSM module, namely SIM800L. In making this system using a microcontroller, namely the Raspberry Pi Pico, and for the programming language using python. Then this tool will drive the servo motor as a plant protector and send SMS notifications to the user. This system is made using a prototype model, which is an open/close notification model for hydroponic plant protectors, this tool can work optimally when water droplets hit the rain sensor field so that the protector can close and send SMS notifications, if conditions are dry then vice versa. Keywords: Hydroponics, rain sensor module, LDR, raspberry pi pico, sms notification.